The Therapy Process Questionnaire ‐ Factor analysis and psychometric properties of a multidimensional self‐rating scale for high‐frequency monitoring of psychotherapeutic processes. (10th July 2019) - Schiepek, Günter; Stöger‐Schmidinger, Barbara; Kronberger, Helmut; Aichhorn, Wolfgang; Kratzer, Leonhard; Heinz, Peter; Viol, Kathrin; Lichtwarck‐Aschoff, Anna; Schöller, Helmut
Abstract: Many outcome measures and session‐related questionnaires in psychotherapy are designed for weekly or biweekly administration. Yet, today, technical developments allow for higher frequency assessments to monitor human change dynamics more closely by daily assessments. For this purpose, the Therapy Process Questionnaire (TPQ) was developed, with a specific focus on inpatient psychotherapy. In this article, we present an explorative and confirmative factor analysis of the TPQ on the basis of the time series data of 150 patients collected during their hospital stay (mean time series length: 69.1 measurement points). A seven‐factor solution was identified, which explains 68.7% of variance and associates 43 items onto the factors, which are "well‐being and positive emotions, " "relationship with fellow patients, " "therapeutic relationship and clinical setting, " "emotional and problem intensity, " "insight/confidence/therapeutic progress, " "motivation for change, " and "mindfulness/self‐care." The internal consistency (Cronbach's α ), the inter‐item correlations of the subscales, and the discriminative power of the items are excellent. The TPQ can be applied in practice and research for creating time series with equidistant measurement points and time series lengths, which are appropriate for the application of nonlinear analysis methods. Especially in clinical practice, it is important to identify precursors of phase transitions, changing synchronization patterns, and critical or instable periods of a process, which now is possible by internet‐ or app‐based applications of this multidimensional questionnaire.